Structural MRI Differences between Patients with and without First Rank Symptoms: A Delusion? - Heering, Henriette D.; Koevoets, Godefridus J. C.; Koenders, Laura; Machielsen, Marise W. J.; Meijer, Carin J.; Kubota, Manabu; de Nijs, Jessica; Cahn, Wiepke; Hulshoff Pol, Hilleke E.; de Haan, Lieuwe; Kahn, Rene S.; van Haren, Neeltje E. M. (Frontiers in Psychiatry, 2015)
Objective: It has been suggested that specific psychotic symptom clusters may be explained by patterns of biological abnormalities. The presence of first rank symptoms (FRS) has been associated with cognitive abnormalities, e.g., deficits in self-monitoring or in the experience of agency, suggesting that a specific network of neural abnormalities might underlie FRS. Here, we investigate differences in cortical and subcortical brain volume between patients with and without FRS. Methods: Three independent patient samples (referred to as A, B, and C) with different mean ages and in different illness stages were included, leading to a total of 348 patients within the schizophrenia-spectrum. All underwent magnetic resonance imaging of the brain. In addition, the presence of FRS was established using a diagnostic interview. Patients with (FRS+, A: n=63, B: n=129, and C: n=96) and without FRS (FRS-, A: n=35, B: n=17, and C: n=8) were compared on global and local cortical volumes as well as subcortical volumes, using a whole brain (cerebrum) approach. Results: Nucleus accumbens volume was significantly smaller in FRS+ as compared with FRS- in sample A (p<0.005). Furthermore, FRS+ showed a smaller volume of the pars-opercularis relative to FRS- in sample B (p<0.001). No further significant differences were found in cortical and subcortical volumes between FRS+ and FRS- in either one of the three samples after correction for multiple comparison. Conclusion: Brain volume differences between patients with and without FRS are, when present, subtle, and not consistent between three independent samples. Brain abnormalities related to FRS may be too subtle to become visible through structural brain imaging.